Comparative craniometric analysis between two species of South American canids and domestic dogs - Fernandes, Rodrigo Antonio [UNESP]; Miam, Isabelle Leite [UNESP]; da Silva Rogério, Guilherme [UNESP]; Del Rio Pinoti, Luciana [UNESP]; Cadioli, Fabiano Antonio [UNESP]; Utsunomiya, Yuri Tani [UNESP] (Springer Nature, 2024)
A comparative craniometric analysis among maned wolves (Chrysocyon brachyurus, n = 9), crab-eating foxes (Cerdocyon thous, n = 8) and domestic dogs (Canis lupus familiaris, n = 124) was performed. A total of 18 craniometric measurements were taken from these specimens, and eight craniometric indices were further computed from those measurements. Using correlation analysis, we found that the 26 variables could be clustered into four groups, namely: (1) indicators of rostro-caudal length; (2) ventro-dorsal height and latero-lateral width; (3) cranial indices; and (4) dimensions of the foramen magnum. Consequently, multivariate techniques were applied to the data in order to reduce dimensionality and thus facilitate the comparisons among domestic and wild species. The projection of the data into the lower-dimensional space created by a principal component analysis showed that skulls of crab-eating foxes resembled small mesaticephalic skulls of domestic dogs, whereas the skulls of maned wolves were closer to those of larger dolichocephalic dogs. However, both species shared similarities with the mesaticephalic and dolichocephalic morphotypes of domestic dogs when variables were considered individually. Importantly, the variation in skull morphology found in the wild specimens was significantly smaller than that found in domestic dogs. These findings suggest an evolutionary constraint to skull shape diversity in maned wolves and crab-eating foxes, which seems consistent with adaptation to a generalist omnivorous diet.
Keywords: Canines; Cerdocyonina; Cranium; Domestication; Musculoskeletal system